Evaluation of Smart Village Program In Sugihwaras Village, Candi District, Sidoarjo Regency - Erika Sri Nurhadi; Indah Prabawati; Tjitjik Rahaju; Tauran T (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The implementation of the Smart Village program in Sugihwaras Village, Candi District, Sidoarjo Regency, adopts a bottom-up approach by utilizing local potential, initiatives, and innovations. This study aims to evaluate the implementation of the Smart Village program within the smart governance pillar by applying William N. Dunn’s policy evaluation framework. The research employs a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model proposed by Miles, Huberman, and Saldana. The findings indicate that the program's effectiveness has not yet been optimal due to disparities in community digital literacy in using village-based digital services. In terms of efficiency, the use of information technology has accelerated administrative services; however, limitations in village officials' technical capacity remain a challenge. About adequacy, the program has succeeded in providing information and administrative services through the village website that support community needs. In terms of equity, digital village services are publicly accessible to the community. Regarding responsiveness, the village government has established complaint mechanisms and demonstrated responsiveness to community needs. Meanwhile, in terms of appropriateness, the program still requires improvement due to the limited and suboptimal assistance provided by the local government.